PENINGKATAN KEAKTIFAN BELAJAR DALAM PEMBELAJARAN SEJARAH MELALUI METODE TEAMS GAMES TOURNAMENT (TGT) DENGAN MEDIA MONOPOLI PADA PESERTA DIDIK KELAS X IPS 2 SMA NEGERI 1 GODEAN - Yermia Rendy Suryadinata (ISTORIA: Jurnal Pendidikan dan Sejarah, 2017)
ABSTRACTThis study aims to (1) find out how to improve learning activeness of students of class X IPS 2 SMA Negeri 1 Godean in learning history through Teams Games Tournament (TGT) method with monopoly media, (2) to know the advantages of application of Teams Games Tournament (TGT) with the monopoly media on the students of class X IPS 2 SMAN 1 Godean. This study is a Classroom Action Research (PTK) which occurs 2 cycles. Each cycle consists of planning, execution, observation, and reflection. Technique of collecting data obtained through observation, questionnaire and also research note. Data analysis uses qualitative analysis that includes data reduction, data presentation, and conclusion. The results showed that (1) Application of Teams Games Tournament (TGT) method with monopoly media can improve the learner activity of class X IPS 1 SMAN 1 Godean. Increased activity in the first cycle of 15.6% occurred from 59.55% to 75.15%. The increase in cycle II of 6.29% occurred from 75.15% to 81.44%. The advantages of applying the Teams Games Tournament (TGT) method with the monopoly media include learners more actively in learning, raising the responsibility of learners to groups and themselves, and training cooperation with other students.Keywords: liveliness, learners, methods, teams games tournament (tgt).